2023
DOI: 10.1038/s41565-022-01311-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional topological magnetic monopoles and their interactions in a ferromagnetic meta-lattice

Abstract: Topological magnetic monopoles, also known as hedgehogs or Bloch points, are threedimensional (3D) nonlocal spin textures that are robust to thermal and quantum fluctuations due to their topology 1-4 . Understanding their properties is of both fundamental interest and practical applications 1-9 . However, it has been difficult to experimentally produce topological magnetic monopoles in a controlled manner and directly observe their 3D magnetization vector field and interactions at the nanoscale.Here, we report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…To showcase the method, we demonstrated the creation and observation of topological magnetic monopoles (TMMs) and their interactions in a nanoscale magnetic metamaterial 3,9,10 . More than 100 stable TMMs are created in a frustrated ferromagnetic meta-lattice.…”
Section: Resultsmentioning
confidence: 99%
“…To showcase the method, we demonstrated the creation and observation of topological magnetic monopoles (TMMs) and their interactions in a nanoscale magnetic metamaterial 3,9,10 . More than 100 stable TMMs are created in a frustrated ferromagnetic meta-lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical simulations of a biological vesicle and experimental results of an aragonite coral sample and an amorphous thin film have shown that RESIRE outperforms FBP, SIRT, and GENFIRE with less peripheral noise, more easily detectable boundaries and features, and reduced missing wedge effects. As the power of RESIRE has been demonstrated with the successful reconstructions of amorphous solids and 3D vector ptychography of magnetic materials 45,46 , we expect that RESIRE can be applied to a wide range of imaging modalities in different disciplines, such as AET 1,3,[5][6][7][8][9][10] , coherent diffractive imaging [16][17][18][19][20][21][22][23][24][25][26][27][28]62,63 , cryo-electron tomography 14,15 , x-ray absorption and phase contrast imaging 2,42,[64][65][66][67][68] , and medical computed tomography 30,34,41…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, the dipolar term does not contribute to stabilizing hedgehog-like BPs. Consequently, this kind of BP can only be stabilized in the absence of dipolar energy and under certain specific conditions 52 , 53 . On the other hand, because does not contribute to a global factor in the magnetostatic field inside the sphere, even spherically symmetric BPs generate a dipolar field inside the nanoparticle.…”
Section: Magnetic Field Of a Bpmentioning
confidence: 99%